A Simple, Quick One-step ELISA Assay for the Determination of Complex Plasma Factor XIII (A2B2) - Katona, Éva; Haramura, Gizella; Kárpáti, Levente; Fachet, József; Muszbek, László (Thrombosis and Haemostasis, 2000)
A new highly sensitive sandwich ELISA assay was developed for the determination of plasma factor XIII (FXIII). Plasma FXIII is a tetrameric complex of two types of subunits (A2B2). A biotinylated monoclonal capture-antibody against the B-subunit and a peroxidase-labelled monoclonal tag-antibody against the A-subunit were added to the plasma dilution and the amount of the complex attached to streptavidincoated microplate was quantitated by measuring peroxidase activity. Only the tetrameric plasma FXIII reacted in the assay, non-complexed A or B subunits showed no reaction. The assay is linear up-to 40 µg/L of FXIII in the assay mixture. It is a quick one-step assay which can be performed within two hours. At normal and low FXIII concentration within batch reproducibility was 2.0% and 3.3%, day to day variation was 5.5% and 8.7%, respectively. Its high sensitivity allows reliable measurement at FXIII concentrations below 1% of normal average. Plasma samples can be stored for the assay at –20° C for at least one month. Plasma levels of healthy individuals were normally distributed and no gender difference was observed. A reference interval of 14-28 mg/L (67-133%) was established.
Keywords: Factor XIII; factor XIII ELISA; factor XIII reference interval